186k views
3 votes
-43 - 4r = 3( 1 - 9r )

2 Answers

4 votes

r = 2

distribute the bracket on the right side of the equation

- 43 - 4r = 3 - 27r

add 27 r to both sides

- 43 - 4r + 27r = 3

- 43 + 23r = 3

add 43 to both sides

23r = 3 + 43 = 46

divide both sides by 23

r =
(46)/(23) = 2


User Red Mak
by
5.1k points
0 votes

-43 - 4r = 3 - 27r

Add 27r to both sides. -43 - 4r + 27r = 3 -27r + 27r or -43 + 23r = 3

Add 43 to both sides. -43 + 43 +23r = 3 + 43 or 23r = 46.

Divide both sides by 23 to get r by itself. 23r / 23 = 46 / 23 or r = 2

r = 2

User BrianLang
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.